First reliable record of a blenny, Petroscirtes springeri (Perciformes: Blenniidae) from the southern coastal waters of Jeju island, Korea - Jung-Hyun An (Journal of Asia-Pacific Biodiversity, 2020)
Three species (Petroscrites breviceps, P. springeri and P. variabilis) belong to the blenny genus Petroscirtes have been recognized from the Korean waters to date. The latter two species of them have been known to be based on underwater photographs without any taxonomic detailed description, not scientific material. Based on a single specimen (80.3 mm SL) collected from a depth of 12 m in the southern coastal waters of Jeju island, P springeri is described in detail as the first reliable record from the Korean waters. The species is characterized by having two dark bluish spots on opercle and caudal fin base, 12 spinous and 21 soft rays on dorsal fin, two spinous and 21 soft rays on anal fin, and a palmate cirrus on lower jaw. We add formally the species into the ichthyfauna of Korea in this study. To avoid confusion in naming of the species, the original Korean name (Du-jeom-be-do-ra-chi) is maintained instead of proposing a new Korean name.